Data Rights di Era Surveillance Capitalism: Skandal Data Cambridge Analytica & Facebook dalam Pemilihan Presiden Amerika Serikat 2016 - Maya Bofa; Darmawan Wawan Budi; Arifin Sudirman (Department of International Relations, Hasanuddin University, 2022)
In 2018, several major British media outlets published the result of a joint investigation which revealed that Cambridge Analytica, a political consulting and data analysis firm, collected about 87 million personal data of Facebook users which was then used without the knowledge of the data owner. This study aims to understand analyze the abuse of data rights involving Cambridge Analytica and Facebook in the 2016 US presidential election. The research method used in this study is descriptive qualitative method. This study found that Cambridge Analytica used personal data of Facebook users for Donald Trump’s digital campaign in the 2016 US presidential election. The data include complete profiles such as name, gender, age, location, status updates, likes, friends, and even personal messages which are then translated into behavioral data. The data collected and analyzed by Cambridge Analytica then became the power in modifying behavior, especially voting behavior. Behavior modification by Cambridge Analytica was possible because the knowledge asymmetry in the use of data. Pada 2018, beberapa media besar Inggris mempublikasikan hasil investigasi bersama yang mengungkap bahwa Cambridge Analytica, sebuah perusahaan konsultan politik dan analisis data, mengoleksi sekitar 87 juta data pribadi pengguna Facebook yang kemudian digunakann tanpa sepengetahuan pemilik data. Penelitian ini bertujuan untuk memahami dan menganalisis penyalahgunaan data rightsyang melibatkan Cambridge Analytica dan Facebook dalam pemilihan presiden Amerika Serikat 2016. Adapun metode yang digunakan dalam penelitian ini adalah kualitatif deskriptif. Penelitian ini menemukan bahwa Cambridge Analytica menggunakan data pribadi pengguna Facebook untuk kepentingan kampanye digital Donald Trump pada pemilihan presiden Amerika Serikat 2016. Data yang diambil meliputi profil lengkap seperti nama, jenis kelamin, usia, lokasi, pembaruan status, likes, teman, bahkan pesan pribadi yang kemudian diterjemahkan menjadi behavioral data. Data yang dikumpulkan dan dianalisis oleh Cambridge Analytica kemudian menjadipower dalam behavioral modification, khususnya voting behavior. Modifikasi tingkah laku oleh Cambridge Analytica dapat dilakukan sebab adanya knowledge asymmetry dalam penggunaan data.